Historische Grundlagen der mobilen Gesellschaft Technologien der Verkehrslenkung und drahtloser Information auf Straßen und Wasserwegen in Europa - Damm, Veit; Henrich-Franke, Christian (Historische Dimensionen Europäischer Integration, 2023)
Modern Europeans are mobile. Cars in particular have made European societies mobile since the 1960s, but, at the same time, mobile Europeans experience their immobility every day when they get stuck in one of countless traffic jams. The reduction of immobility has therefore been a major scientific and societal challenge since the beginning of mass mobility, in order to minimise its negative consequences, such as individual time loss or economic damage. This volume addresses these challenges by bringing together interdisciplinary approaches to researching the history of traffic information systems as instruments of congestion avoidance and traffic control. It addresses the developmental processes, designs and designers of such systems from traffic radio to digital navigation. With contributions by Katja Berg, Fritz Bolte, Weert Canzler, Christoph Classen, Veit Damm, Jens-Ivo Engels, Manfred Grieger, Christian Henrich-Franke, Thomas Kusche-Knežević, Rüdiger Malfeld, Oliver Michler, Marco Secci and Jörg Wehling.